Fatty acids composition of selected Malaysian fishes (Komposisi asid lemak ikan terpilih Malaysia) - Nur Airina Muhamad; Jamaludin Mohamad (Universiti Kebangsaan Malaysia, 2012)
A comparative study on the fatty acids contents of three Malaysian marine fishes Tenualosa toli (Terubok), Rastrelliger kanagurta (Kembong), Stolephorus baganensis (Bilis) and three freshwater fishes Channa striatus (Haruan), Pangasius hypothalamus (Patin), Clarias macrocephalus (Keli) were carried out. Marine fishes showed more unsaturated fatty acids with 3, 4, 5 and 6 double bonds than in freshwater fishes. Two n-3 polyunsaturated fatty acids (PUFAs); eicosapentaenoic acid (EPA) and docasahaexaenoic acid (DHA) were found more in marine fishes PUFAs than in freshwater fishes. Based on the fatty acids content of DHA, EPA and arachidonic acid (AA), Stolephorus baganensis provides the best source of it (4.68%,10.5%, 4.68%) followed by Rastrelliger kanagurta (10.62%, 4.85%, 3.17%) and Tenualosa toli (9.93%, 2.50%, 0.16%). However, freshwater fishes showed small range of DHA (0.63% - 1.41%), EPA (0.11% - 0.25%) and AA (1.41% - 4.46%). Saturated fatty acids palmitic was the major fatty acid found in all fishes studied.